PERBANDINGAN PRODUKTIVITAS ALAT KERJA SLIPFORM PAVER, SEMI SLIPFORM PAVER PADA PEKERJAAN RIGID PAVEMENT - Suyadi, Didik Eko; Firdaus, Firdaus (Ensiklopedia Education Review, 2023)
Study This aim For analyze Comparison of Productivity of Slipform Paver Work Tools And Semi Slipform Paver On Rigid Pavement Work in the PPP project P reservation Activities for the East Sumatra Highway. Approach used in study This that is descriptive quantitative, with technique data collection used that is observation, interview and documentation (project RAB). From research This obtained results that the average productivity of the Gumacho 450 is 16.1 m³/hour with a rigid pavement thickness of 0.305 m' and a stretch width of 4 m. The paver tool used is Gomaco 450. The productivity value of the paver tool is 52.78 m²/hour. While the average productivity of the Wirgen SP 500 is 35.23 m³/hour with a rigid pavement thickness of 0.305 m and a width of 4 m. The paver tool used is Wirgen SP 500. The productivity value of the paver tool is 115.51 m²/hour. As well as the factors that influence productivity Rigid Pavement work, namely weather, procurement of goods at the time material goods (cement, rebar, and bricks) arrived to location, Material Distance, Managerial Factors and the effectiveness of working hours.Keywords: Productivity tool work, Rigid Pavement Work